Peran Majelis Gereja Mengajarkan Doktrin Keselamatan Kepada Warga Jemaat Gereja Toraja Jemaat Meriba Surruk dalam Bingkai Biblika Kontekstual - Nober Patongloan (Jurnal Apokalupsis, 2023)
The church assembly is one of the elements that influences the understanding of the faith of the congregation members. Therefore, the church assembly is expected to be able to provide true faith teaching to its citizens. Therefore, to be able to achieve teaching of faith that is in accordance with the Bible as the basis for teaching, contextual biblical studies are the answer. Contextual Bible can be used as an answer to the teaching of true and biblical faith. Therefore, the purpose of this paper is to describe the benefits of contextual biblical studies for church councils in their duties among the congregation in teaching Christian doctrine which in this paper focuses on the doctrine of salvation. The method used is a qualitative method with results showing that the church assembly really needs contextual biblical studies where these results were obtained through research at the Toraja Congregation Meriba Surruk Church which showed misunderstandings by congregation members regarding the doctrine of salvation as a result of a lack of correct understanding from the church assembly.